Electrophoretic co-deposition of diamond/borosilicate glass composite coatings - Boccaccini, Aldo R.; et al. (Surface & Coatings Technology, 2007)
Composite coatings made of diamond powders and borosilicate glass have been deposited on stainless steel substrates by electrophoretic co-deposition. Ethanol and acetone suspensions containing diamond powders of particle size 1-2 μm and borosilicate glass powders of size 0.1-0.5 μm were used. Electrophoretic deposition (EPD) parameters were optimized by a trial-and-error-approach. Microstructures of deposited and sintered coatings were investigated by XRD and SEM analysis. The results show that applied voltages up to 10 V led to thin and incomplete coatings. Voltages higher than 50 V resulted in uneven coatings with uncontrolled thickness and poor uniformity. The best results were achieved using ethanol suspensions. Smooth, uniform and dense coatings with diamond and glass particles distributed uniformly were obtained under applied voltages in the range of 30-50 V and a deposition time of 4 min. The concentration ratio of diamond to borosilicate glass in the composite coatings was in good correlation with the original ratio in suspension, thus control of the coating microstructure and composition is possible. During sintering at 900 °C, the glass particles softened; sintered by viscous flow and spread over the diamond particles surface. Thus a glass layer forms protecting the diamond from oxidization or graphitization and bonding the diamond particles together. © 2007 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2007.tech.IW.LM.electr
Keywords: Borosilicate glass coatings; Diamond; Electrophoretic deposition